2016
DOI: 10.1021/acs.jpcc.6b04696
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Influence of Drop Size and Surface Potential on the Contact Angle of Ionic-Liquid Droplets

Abstract: In this work we have performed molecular dynamics simulations of the room temperature ionic-liquid 1-ethyl-3-methylimidazolium tetrafluoroborate on a surface with graphene structured sheets. Contact angles were calculated via polynomial-fitting of two dimensional atomic density contours. Drop size and surface interaction were varied to assess their influences on the contact angle. At low graphene interaction potential no change in contact angle with drop size was found. When increasing the surface interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Here, we characterize the dewetting thermodynamics of IL [EMIM] [BF 4 ] in nanoscale confinement between model solvophobic surfaces, whose interactions with the IL are chosen to yield a contact angle of approximately 140 • . 63 We find that enhanced density fluctuations at the surface of solvophobic plates can reduce free energy barriers, similar to previous investigations involving water. Our findings additionally suggest that confinement-induced changes in interfacial structure can significantly impact the free energy barrier to capillary evaporation.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we characterize the dewetting thermodynamics of IL [EMIM] [BF 4 ] in nanoscale confinement between model solvophobic surfaces, whose interactions with the IL are chosen to yield a contact angle of approximately 140 • . 63 We find that enhanced density fluctuations at the surface of solvophobic plates can reduce free energy barriers, similar to previous investigations involving water. Our findings additionally suggest that confinement-induced changes in interfacial structure can significantly impact the free energy barrier to capillary evaporation.…”
Section: Introductionsupporting
confidence: 89%
“…(2)]. 63,[80][81][82] We conclude by noting that small changes in the flexibility of confining plates, not included here, can significantly impact the thermodynamics and kinetics of capillary evaporation 60 and can be used to further tune solvophobic effects in IL-based systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low forces in non-contact techniques are especially useful for liquid surfaces. AFM has for example been used to determine the contact angle of nano-sized IL droplets on a silicon wafer [22], to investigate liquid interfaces [23], and to elucidate the hydrodynamics in boundary layers around micro-and nanofibers [24]. The absence of neutral molecules, and the nanoscale, are great stimuli for theoretical approaches and for simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Results show that contact angle hysteresis increases with increasing the surface roughness and degree of wetting. Burt et al [21] studied the e ect of drop size and surface interaction on the contact angle of ionic-liquid droplets by molecular dynamics simulations. Their study revealed that there was no change in contact angle with drop size at low interaction potential.…”
Section: Introductionmentioning
confidence: 99%